THE CONTRIBUTION OF UMWARIMU SACCO TO THE WELFARE OF TEACHERS IN RWANDA: A SOCIO-WELFARE STUDY /ASSESSMENT. - Leandre Mushinzimana; Achmad Faisal (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
Loan mobilization must be a component of any development effort because it is thought to be the most efficient way to raise productivity and living standards while attempting to end teacher poverty. The study aimed to investigate how SACCO cooperative strategies impacted members to get a loan and look into factors influencing teachers’ socio-welfare in Rwanda. A sample of 15 SACCOs out of 30 in the Rwanda region and 180 SACCO members out of 72,334 were used in the study. These were chosen using straightforward random sampling techniques. The data was collected using a questionnaire, which 100 respondents answered. Data were analyzed using an SEM with AMOS to test relationships and assess the factors influencing teachers’ socio-welfare in Rwanda. According to the correlation coefficient, model fitness, regression weights, and hypothesis, the loan requirement positively impacted socio-welfare. In contrast, loans and intervening variables had a significantly positive effect. Loan and intervening variables were the most significant variables at a 100% confidence level. Therefore, most of them are seen as SACCOs, similar to cooperatives, because they impact members’ socio-welfare of teachers.